(untitled) (Simbiótica. Revista Eletrônica, 2025)
This article proposes an analysis of the mobilizations of digital platform workers in the context of the Covid-19 pandemic, a period when the vulnerabilities of this category were brought to light. By examining the acts carried out by platform workers in Brazil between 2019 and 2020, using the Protest Event Analysis (PEA) methodology, we aim to understand the main characteristics of these events, highlighting the leadership of delivery workers in the struggle for rights, which culminated in the movement known as “Breque dos Apps”. The analysis of the temporal distribution, the actors involved, the demands, the tactics, the locations of occurrence, and the repression in the protest events revealed significant changes in the variables over the studied period, demonstrating a correlation between the pandemic and these transformations. In addition to providing an overview of the Brazilian scenario, this article maps, analyzes, and interprets a large number of protests, offering data that can be used in future comparative studies.